2013
DOI: 10.1016/j.jacc.2013.02.074
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Impairs Exercise Training Adaptations

Abstract: OBJECTIVES Determine if simvastatin impairs exercise training adaptations. BACKGROUND Statins are commonly prescribed in combination with therapeutic lifestyle changes, including exercise, to reduce cardiovascular disease risk in patients with the metabolic syndrome. Statin use has been linked to skeletal muscle myopathy and impaired mitochondrial function, but it is unclear whether statin use alters adaptations to exercise training. METHODS We examined the effects of simvastatin on changes in cardiorespir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
156
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(170 citation statements)
references
References 40 publications
7
156
0
7
Order By: Relevance
“…Furthermore, some 20,21 but not all studies [22][23][24] suggest that improvements in cardiorespiratory fitness in response to exercise training may be blunted by statin therapy. Therefore, in the current study we sought to assess the impact of cardiorespiratory fitness on the incidence of type 2 diabetes in dyslipidemic patients treated with statins.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some 20,21 but not all studies [22][23][24] suggest that improvements in cardiorespiratory fitness in response to exercise training may be blunted by statin therapy. Therefore, in the current study we sought to assess the impact of cardiorespiratory fitness on the incidence of type 2 diabetes in dyslipidemic patients treated with statins.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Cardiorespiratory fitness was assessed by a standard treadmill test using the Bruce protocol at the Veterans Affairs Medical Center in Washington, DC, and an individualized ramp protocol as described previously 20 for subjects assessed at the Veterans Affairs Health Care System Center in Palo Alto, CA. Peak exercise capacity (Metabolic Equivalents) was estimated by use of standardized equations.…”
Section: Assessments Of Exercise Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mikus et al reported recently that statin-treated subjects did not benefit from the training effect of a 12-week exercise program. In a randomized, placebo-controlled trial among 41 subjects, those treated with simvastatin showed significant failure to increase peak oxygen consumption and, in muscle biopsy specimens, a significant lack of increase in an enzyme marker of mitochondrial content [7].…”
mentioning
confidence: 99%
“…Is there any interaction between statins and the natural decline of strength with aging? The recent data of Mikus et al may be pertinent [7]. What are optimal doses for lifelong statin treatment?…”
mentioning
confidence: 99%